Computational fluid dynamic modelling of two phase flow on a hydrocyclone - Leeuwner, M.; Eksteen, Jacques (Southern African Institute of Mining and Metallurgy, 2008)
Computational fluid dynamic (CFD) modelling is used to research the complex flow structures that exist in a hydrocyclone. By simulation of a two phase (water and air) flow system, the internal flow and multiphase interactions are investigated. The suitability of CFD modelling as a design tool is further evaluated by examining the effect of varying device dimensions. Three hydrocyclone geometries, used in previous studies, are specified. A transient simulation approach, which employs the Reynolds Stress Model as turbulence model and the Volume of Fluid model as multiphase model, is followed. Results are validated qualitatively against experimental measurements from the previous studies